PENINGKATAN KAPABILITAS ’’ENTREPRENEURSHIP OF SMECTRA’’ DALAM MENGHADAPI ERA INDUSTRI 5.0 - Aries Kurniawan; Beni Dwi Komara; Elif Nashikhatul Maziyah; Djoko Soelistya (DedikasiMU : Journal of Community Service, 2023)
SMK NU Gresik has 736 students with the number of graduations reaching 225 per year. However, the development of IT (Information Technology) and globalization has influenced companies to innovate in industrial automation. As a result, less job opportunities and reduced absorption of SMK NU Gresik graduates in IDUKA (Industrial and Business World). The location plan for the implementation of the Community Partnership Program (PKM) is at the Gresik NU SMK which has the potential to carry out entrepreneurial development activities and business development. In addition, SMK NU Gresik has the potential to become a school that produces entrepreneurs by embedding entrepreneurial concepts holistically or involving cognitive, affective and psychomotor domains. Entrepreneurship lessons should be provided with a larger and more dominant portion when compared to other subjects that are oriented towards cognitive intelligence. The objectives of implementing PKM activities are; 1. Prepare students to enter the workforce and business world and develop a professional attitude. 2. Prepare students to be able to choose careers, be competent and able to develop themselves. 3. Preparing the middle level workforce to fill the needs of industry and the world of work at this time and in the future. 4. Prepare graduates to become productive, adaptive and creative citizens with a science and technology perspective. Through coaching in this PKM program, it can improve entrepreneurial spirit and skills so that they are ready to enter the industrial world and the business world.